Tumor microenvironment participates in metastasis of pancreatic cancer - Ren, Bo; Cui, Ming; Yang, Gang; Wang, Huanyu; Feng, Mengyu; You, Lei; Zhao, Yupei (Molecular cancer, 2018)
Pancreatic cancer is a deadly disease with high mortality due to difficulties in its early diagnosis and metastasis. The tumor microenvironment induced by interactions between pancreatic epithelial/cancer cells and stromal cells is critical for pancreatic cancer progression and has been implicated in the failure of chemotherapy, radiation therapy and immunotherapy. Microenvironment formation requires interactions between pancreatic cancer cells and stromal cells. Components of the pancreatic cancer microenvironment that contribute to desmoplasia and immunosuppression are associated with poor patient prognosis. These components can facilitate desmoplasia and immunosuppression in primary and metastatic sites or can promote metastasis by stimulating angiogenesis/lymphangiogenesis, epithelial-mesenchymal transition, invasion/migration, and pre-metastatic niche formation. Some molecules participate in both microenvironment formation and metastasis. In this review, we focus on the mechanisms of pancreatic cancer microenvironment formation and discuss how the pancreatic cancer microenvironment participates in metastasis, representing a potential target for combination therapy to enhance overall survival.